Towards sustainable highland banana production in Uganda: Opportunities and challenges - Nyombi, K. (African Journal of Food, Agriculture, Nutrition and Development, 2013)
East Africa highland bananas ( Musa sp., AAA- EA HB) are an important starchy food and cash crop in Uganda and the Great Lakes region of East Africa. Widespread reports of declining yields in Uganda since the 1930s and the low yields today do raise serious sustainability and food security concerns , especially as food demand increases with a population growth rate of 3.2% per annum . In addition, increasing urbanization continues to increase pressure on the banana system s, with bunches and leaves increasingly transported from rural areas to urban centres, leading to the continued loss of nutrients especially potassium. Actual yields on many smallholder banana farms (5 − 20 Mg ha − 1 yr − 1 FW ) in Uganda are far below the estimated potential yield (100 Mg ha − 1 FW ). Farmers cite soil fertility decline, pests ( banana weevils and nematodes) and moisture stress as the major factors responsible for yield decline. In response, several organic and mineral fertilization experiments have been carried out at research stations and in farmers’ fields in Uganda since the 1950s . Researchers have mostly reported responses to organic fertilizers, no or poor responses to Mg and P fertilization with some responses to K and N fertilization , but with yields that are far below the estimated potential . Although pests are controlled in so me trials, researchers have often failed to embrace a systems approach , quite often leaving out factors, such as moisture stress and soil physical conditions that affect the responses to fertilization . The government of Uganda in the National Development Plan 2010/11−2014/15 targets increased agricultural productivity for key staple crops like bananas in alleviating poverty in rural areas and ensuring national food security. In order to set proper banana research priorities to benefit farmers in Uganda , the objectives of this study were : to review past research aimed at reducing banana production constraints , identify opportunities and challenges facing the banana sector and put forward new research perspectives.